ADHERENCE OF HEALTHCARE STAFF TO INFECTION PREVENTION AND CONTROL GUIDELINES IN THE GOVERNMENT HEALTH SECTOR IN THE KINGDOM OF SAUDI ARABIA - Ali Saleh Ali Qaiman, Nouf Eid Bijad Al-Mutairi, Khaled Saleh Abdullah Alghamdi, -Mansour Mana Nasser Al Mordef, -Monera Abdulla Hussain Al Mokalas, Mohammad Mahdi Saleh Al Harth,,; Yahya Mesfer Mohammed Al Hussin, ‏‏ Abdullah Mana Mahdi Alyami, Tariq Saud N Alshammari, Muslih Mahdi M Al Yami, (Chelonian Research Foundation, 2022)
Objectives: This study aimed to evaluate the adherence Of healthcare staff (HCSs) in the government health sector in Saudi Arabia to infection prevention and control (IPC) practices and to identify the factors that influence their compliance, utilizing the Health BeliefModel as the theoreticalframework. Design: The research utilized quantitative data from an explanatopy sequential mixedmethods study. Participants and settings: Between May 17 and August 30, 2022, a total of 604 healthcare stafffrom randomly selected tertiary carefacilities in the government health sector in Saudi Arabia participated in the study. Primary' and secondary outcome measures: The primary outcome was the level of compliance with the IPC guidelines provided by the World Health Organization (WHO), along with identifying the associatedfactors influencing compliance. Results: The study revealed a mean compliance score of 0.49 (+0.25) on a scale of O to 1. HCSs demonstrated the highest compliance with medical mask wearing guidelines (81%) and the lowest compliance with high-touch surface decontamination regulations (23%). Compliance with IPC guidelines were significantly associated with factors such as increasing age, female sex, working as a nurse, having non-communicable diseases, and previous exposure to patients with COVID-19. Compliance was positively associated with peweived benefits (B=O.()39, 95% CI 0.001 to 0.076), self-efficacy 95% CI 0.060 to 0.142), and cues to action (B=().045, 95% CI 0.002 to 0.088). Participants who reported low peweived barriers had O. 061 times greater compliance with IPC guidelines compared to those with high perceived barriers. Conclusion: The overall compliance with WC' guidelines among HCSs in the government health sector in Saudi Arabia was found to be unsatisfactory. The study highlights the importance of emphasizing self-efficacy in interventions aimed at improving HCSs' adherence to IPC practices. Additionally, interventions should address perceived barriers, including unreliable information sources, unsafe working conditions, and inadequate availability ofpersonal protective equipment. Furthermore, cues to action, such as trust in the administration and the provision of adequate IPC guidance, should be considered in interventions to enhance compliance. Keywords: public health, infection control, preventive medicine.